Stigma, social reciprocity and exclusion of HIV/AIDS patients with illicit drug histories: A study of Thai nurses' attitudes - Stoové Mark A; Chan Kit; Reidpath Daniel D (BMC, 2008)
Abstract Background Stigma is a key barrier for the delivery of care to patients living with HIV/AIDS (PLWHA). In the Asia region, the HIV/AIDS epidemic has disproportionately affected socially marginalised groups, in particular, injecting drug users. The effect of the stigmatising attitudes towards injecting drug users on perceptions of PLWHA within the health care contexts has not been thoroughly explored, and typically neglected in terms of stigma intervention. Methods Semi-structured interviews were conducted with a group of twenty Thai trainee and qualified nurses. Drawing upon the idea of 'social reciprocity', this paper examines the constructions of injecting drug users and PLWHA by a group of Thai nurses. Narratives were explored with a focus on how participants' views concerning the high-risk behaviour of injecting drug use might influence their attitudes towards PLWHA. Results The analysis shows that active efforts were made by participants to separate their views of patients living with HIV/AIDS from injecting drug users. While the former were depicted as patients worthy of social support and inclusion, the latter were excluded on the basis that they were perceived as irresponsible 'social cheaters' who pose severe social and economic harm to the community. Absent in the narratives were references to wider socio-political and epidemiological factors related to drug use and needle sharing that expose injecting drug users to risk; these behaviours were constructed as individual choices, allowing HIV positive drug users to be blamed for their seropositive status. These attitudes could potentially have indirect negative implications on the nurses' opinions of patients living with HIV/AIDS more generally. Conclusion Decreasing the stigma associated with illicit drugs might play crucial role in improving attitudes towards patients living with HIV/AIDS. Providing health workers with a broader understanding of risk behaviours and redirecting government injecting drug policy to harm reduction are discussed as some of the ways for stigma intervention to move forward.